2019
DOI: 10.1016/j.jom.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and productivity in product design for additive manufacturing: Mechanisms and platform outcomes of remixing

Abstract: The present study explores the phenomenon of remixing in product design for additive manufacturing (AM). In contrast to other manufacturing techniques, AM offers unprecedented flexibility in adapting existing product designs to changing requirements. However, in order to benefit from this potential, structured design procedures and tools are indispensable. As a possible solution, online platforms for collaborative 3D model creation are increasingly implementing features for remixing, a concept describing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 102 publications
0
51
0
1
Order By: Relevance
“…A central thread of the articles in the special issue (SI) is the bridging of physical and digital spheres that derives from the encapsulation of product design and production‐process information into unique digital artifacts: “digital encapsulation.” Digital encapsulation is addressed in all the SI articles but is particularly salient in Friesike et al () and Hedenstierna et al (). These articles explore the use of digitally encapsulated artifacts to revisit established design and manufacturing processes, and provide examples of how digital encapsulation can open new avenues for theory elaboration in OSCM.…”
Section: Review Of the Special Issue Contributions: Digital Encapsulamentioning
confidence: 99%
See 3 more Smart Citations
“…A central thread of the articles in the special issue (SI) is the bridging of physical and digital spheres that derives from the encapsulation of product design and production‐process information into unique digital artifacts: “digital encapsulation.” Digital encapsulation is addressed in all the SI articles but is particularly salient in Friesike et al () and Hedenstierna et al (). These articles explore the use of digitally encapsulated artifacts to revisit established design and manufacturing processes, and provide examples of how digital encapsulation can open new avenues for theory elaboration in OSCM.…”
Section: Review Of the Special Issue Contributions: Digital Encapsulamentioning
confidence: 99%
“…In the study titled “Creativity and productivity in product design for additive manufacturing,” Friesike et al () study Thingiverse, the open‐source maker community, to examine the interactions between designers and users of the designs, in an open‐system context. Their analysis of over 200,000 open designs and design improvements for AM examined specifically the degree and mode of reuse improvement.…”
Section: Review Of the Special Issue Contributions: Digital Encapsulamentioning
confidence: 99%
See 2 more Smart Citations
“…Hasan et al ( 2013 ) conducted interviews and found that 30% of companies only partly owned the CAD data for the products they sell. Rogers et al ( 2016 ) showed that a design file can either be retrieved from scanning an existing part, making a new construction or downloading the file from a database such as Thingiverse (Friesike et al 2018 ). In this way, either the customer, the manufacturing firm or a generative service provider can create the CAD file by themselves or in collaboration.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%